Isolation and purification of Huperzine A - SHEN Sheng-rong; Yu Hai-ning; JIN Chao-fang; XU Yue-rong (浙江大学学报. 农业与生命科学版)
Technique of isolation and purification of Huperzine A from Huperzia serrata (Thunb) Trev. was studied in this paper. To get rid of some pigments and other impurities, some of chemical techniques for separation such as extraction with organic acid, absorption with charcol and re-crystallization with chloroform were employed. The results suggested that: ① pH value seriously influenced Huperzine A in solution; ② There are ideal procedures with extraction under the certain environment of pH value; ③ Charcol plays an important role in the process; ④ The measurement of re-crystallization had crucial role in promoting the purity of Huperzine A.